1995
DOI: 10.1182/blood.v86.7.2856.2856
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for Fanconi anemia

Abstract: Fanconi anemia is a genetic disorder associated with diverse congenital abnormalities, progressive bone marrow failure, and increased risk of leukemia and other cancers. Affected persons often die before 30 years of age. Bone marrow transplantation is an effective treatment, but there are few data regarding factors associated with transplant outcome. We analyzed outcomes of HLA-identical sibling (N = 151) or alternative related or unrelated donor (N = 48) bone marrow transplants for Fanconi anemia performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…This early clinical experience prompted in vitro laboratory studies that confirmed the hypersensitivity of FA cells to CY Auerbach et al, 1983) and irradiation (Gluckman et al, 1984). As a result, Gluckman et al proposed the use of lowdose CY (20 mg/kg) and a single fraction of thoraco-abdominal irradiation [(TAI), 500 cGy] conditioning regimen, leading to markedly reduced RRT with enhanced survival after human leucocyte antigen (HLA)-matched sibling donor HCT (Gluckman et al, 1984). Over the last two decades, efforts have focused on ways to improve upon these early experiences with sequential changes to the preparative therapy.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…This early clinical experience prompted in vitro laboratory studies that confirmed the hypersensitivity of FA cells to CY Auerbach et al, 1983) and irradiation (Gluckman et al, 1984). As a result, Gluckman et al proposed the use of lowdose CY (20 mg/kg) and a single fraction of thoraco-abdominal irradiation [(TAI), 500 cGy] conditioning regimen, leading to markedly reduced RRT with enhanced survival after human leucocyte antigen (HLA)-matched sibling donor HCT (Gluckman et al, 1984). Over the last two decades, efforts have focused on ways to improve upon these early experiences with sequential changes to the preparative therapy.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The conditioning regimens were based upon those administered to patients with acquired aplastic anaemia, most often consisting of cyclophosphamide (CY) 200 mg/kg with or without irradiation and resulted in excessive regimen-related toxicity (RRT), severe acute graft-versus-host disease (GVHD) and poor survival (Gluckman et al, , 1983. This early clinical experience prompted in vitro laboratory studies that confirmed the hypersensitivity of FA cells to CY Auerbach et al, 1983) and irradiation (Gluckman et al, 1984). As a result, Gluckman et al proposed the use of lowdose CY (20 mg/kg) and a single fraction of thoraco-abdominal irradiation [(TAI), 500 cGy] conditioning regimen, leading to markedly reduced RRT with enhanced survival after human leucocyte antigen (HLA)-matched sibling donor HCT (Gluckman et al, 1984).…”
Section: Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the increased sensitivity to cyclophosphamide and radiation, and the risk of later malignancy, attention has focused on determining an optimal conditioning regimen for FA. However, because of the rarity and genetic heterogeneity of the syndrome, this problem has proved very difficult (Hows et al, 1989;Flowers et al, 1996;Gluckman, 1996).…”
Section: Discussionmentioning
confidence: 99%